Marxist Explanations of the Rise of Contemporary Oligarchy - Tsakova, Ivka (Research Papers, 2018)
The ideas of Karl Marx experience a renaissance in the contemporary world of neoliberal global capitalism. The thesis of the state as a “weapon of class dominance” is especially current in the process of oligarchization of politics under the mask of liberal democracy. We try to explain the rise of the contemporary oligarchy with the methodology of Marxism (neomarxism). The content is structured around three statements: a) The oligarchs are treated as a class; b) Oligarchy is legitimized with ideology; c) Current capital accumulation has reached unprecedented concentration in the hands of the few. The conclusion draws paths for anti-oligarchic resistance.